Knowing What’s Out There: Awareness of Non-Alcoholic Fatty Liver Disease - Ghevariya, Vishal; Sandar, Nan; Patel, Kishor; Ghevariya, Nehal; Shah, Ruchit; Aron, Joshua; Anand, Sury (Frontiers in Medicine, 2014)
Background: Non Alcoholic Fatty Liver Disease (NAFLD) is the most common hepatic disorder, which poses a significant health burden in the western countries. As the epidemic of obesity slides health downward, the incidence of NAFLD is evidently increasing. Aims: We aimed to ascertain the awareness of NAFLD and its risk factors in the general population, which may be helpful in designing educational tools to promote prevention, early detection and treatment of this disorder. Methods: A survey of 5000 non-institutionalized residents of Brooklyn, NY was conducted. Sixteen items were included in the survey questionnaire including awareness of fatty liver, predisposing factors of NAFLD, awareness of cirrhosis, and conditions that advance to cirrhosis. The questionnaire also addressed awareness of prevention, diagnostic methods and treatment of NAFLD and education of physicians to their patients about NAFLD. Results: Overwhelming majority of the subjects was not aware of NAFLD and stated that their physicians did not have a discussion about NAFLD. Conclusion: NAFLD is a preventable liver disorder with limited treatment options. Thorough counseling by primary care physicians can be of paramount importance in preventive strategy for NAFLD. We should target our teen-age population in an era of obesity epidemics of all times.